Assessment tools to measure postnatal mental illness: a 10-year scoping review - Ruslan, Nur Liyana Shahmi; Mohd Arifin, Siti Roshaidai; Abang Abdullah, Khadijah Hasanah; Abas, Nurul Ain Hidayah; Husain, Rohayah; Abd. Aziz, Karimah Hanim; Musa, Ramli; Syed Mohideen, Fathima Begum; Perveen, Asma; Che Mat, Khairi (Academy of Family Physicians of Malaysia, 2022)
Introduction: The use of assessment tools to measure postnatal mental illness is essential in healthcare settings. However, variations in the types of tools and their reliability in a particular population lead to under-recognition of mental health status in postnatal mothers. The aim of this review is to evaluate the most recent 10 year of research on the validity and reliability of postnatal mental illness assessment tools. Methods: A literature search of studies from online databases PubMed, Scopus, and Science Direct was conducted. Results: A total of 59 studies were selected for this review. Several studies utilised multiple assessment tools, and a total of 96 assessment tools were identified and classified into six domains: postnatal blues, postnatal stress, postnatal anxiety, postnatal depression, postnatal psychosis, and postnatal psychological disorder. In this review, EPDS was the most common tool used to identify postnatal depression and anxiety while DASS 21 was the most common tool used to identify postnatal psychological disorder. There is a wide range in preponderance of evidence for the reliability of each assessment tool and there were inconsistencies in assessing the validity of the assessment tools. Conclusion: This review provides information regarding some of the main assessment tools currently available to measure postnatal mental illnesses. There were no standardised tools that were used in a particular setting. The results may differ in different population because there are differences in not only languages and dialects, but also cultural and racial backgrounds, which greatly influences their perception and interpretation of postnatal mental illness.